Role of insulin as a growth promoter in regulating the response of curcumin in human primary gingival fibroblasts: An in vitro study - Dixit Jaya; Verma Umesh; Karamjeet; Sharma Ramesh; Balapure Anil (Wolters Kluwer Medknow Publications, 2009)
Background: The aim of this investigation was to evaluate the biochemical and morphologic changes in human primary gingival fibroblasts (hPGF) treated with curcumin (CUR) and insulin (I) plus curcumin (CUR) in a dose-dependent fashion. Materials and Methods: Human gingival fibroblasts were obtained from gingival biopsies. Curcumin was dissolved in ethanol, diluted with Dulbecco′s modified Eagle′s medium (DMEM) to obtain dilutions and bovine insulin was dissolved in 0.01 N HCl and diluted with DMEM. Cells were exposed to different concentrations of CUR and insulin (1 µg/ml) plus CUR for next 48 hours at 37°C and cellular growth profile was assessed using sulforhodamine-B (SRB), 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) and fluorescence-activated cell sorter (FACS). Results: The cell viability in both the treatments at lower concentrations of SRB (1 and 10 µM) and MTT (1 µM) were found to be significantly higher than that observed at higher concentrations, while apoptosis in both the treatments at lower concentrations was observed to be significantly lower than at higher concentrations. Also, the cell viability of I + CUR at lower concentrations of SRB (1, 10 and 25 µM) and MTT (1 µM) were found to be significantly higher than the respective CUR, while apoptosis at higher concentrations (50, 75 and 100 µM), especially at 75 µM was significantly low. The IC 50 of I + CUR of SRB, MTT and FACS were 1.1, 1.0 and 1.4 times higher than respective concentrations of CUR. Conclusions: Insulin (1 µg/ml) exerted cytoproliferative and curcumin exerted cytocidal effects (in a dose-dependent manner) on hPGF. Insulin (1 µg/ml) and curcumin at different concentrations when added together decreased the cytocidal effect of curcumin.